Development of Bioinspired Gelatin and Gelatin/Chitosan Bilayer Hydrofilms for Wound Healing - Itxaso Garcia-Orue; Edorta Santos-Vizcaino; Alaitz Etxabide; Jone Uranga; Ardeshir Bayat; Pedro Guerrero; Manoli Igartua; Koro de la Caba; Rosa Maria Hernandez (MDPI AG, 2019)
In the current study, we developed a novel gelatin-based bilayer wound dressing. We used different crosslinking agents to confer unique properties to each layer, obtaining a bioinspired multifunctional hydrofilm suitable for wound healing. First, we produced a resistant and non-degradable upper layer by lactose-mediated crosslinking of gelatin, which provided mechanical support and protection to overall design. For the lower layer, we crosslinked gelatin with citric acid, resulting in a porous matrix with a great swelling ability. In addition, we incorporated chitosan into the lower layer to harness its wound healing ability. FTIR and SEM analyses showed that lactose addition changed the secondary structure of gelatin, leading to a more compact and smoother structure than that obtained with citric acid. The hydrofilm was able to swell 384.2 ± 57.2% of its dry weight while maintaining mechanical integrity. Besides, its water vapour transmission rate was in the range of commercial dressings (1381.5 ± 108.6 g/m2·day). In vitro, cytotoxicity assays revealed excellent biocompatibility. Finally, the hydrofilm was analysed through an ex vivo wound healing assay in human skin. It achieved similar results to the control in terms of biocompatibility and wound healing, showing suitable characteristics to be used as a wound dressing.